Investigation of Ionic Conductivity of Electrolytes for Anode-Free Lithium-Ion Batteries by Impedance Spectroscopy - Azhar Abdrakhmanova; Alfira Sabitova; Binur Mussabayeva; Bulbul Bayakhmetova; Zhanna Sharipkhan; Elmira Yermoldina (Electrochem)
Anode-free lithium-ion batteries offer a volumetric energy density approximately 60% higher than that of conventional lithium-ion cells. Despite this advantage, they often experience rapid capacity degradation and a limited cycle life. Optimizing electrolyte formulations—particularly through the use of specific additives, solvents, and lithium salts—is essential to improving these systems. This study explores electrolytes composed of fluorinated and carbonate-based solvents applied in anode-free lithium-ion cells featuring copper as the anode substrate and Li1.05Ni0.33Mn0.33Co0.33O2 as the cathode. In the present work, the ionic conductivity of electrolytes was studied by impedance spectroscopy, and the electrochemical parameters of anode-free lithium-ion cells were compared using these electrolyte solutions: lithium difluoro(oxalato)borat (LIDFOB) salts were used in a mixture of solvents such as fluoroethylene carbonate (FEC) and dimethoxyethane (DME) in a ratio of 3:7 and in a mixture of propylene carbonate (PC) and dimethoxyethane in a ratio of 3:7. Enhanced performance was observed upon the substitution of conventional carbonates with fluorinated co-solvents. The findings suggest that LiDFOB is a thermostable salt, and its high conductivity contributes to the formation and stabilization of the interface of solid electrolytes. The results indicate that at low temperature conditions, a double salt should be used for lithium current sources, for example, 0.4 M LiDFOB and 0.6 M LiBF4, as well as electrolyte additives such as fluoroethylene carbonate and lithium nitrate.